Supplementary tables:MetaFetcheR: An R package for complete mapping of small compound data - Yones, Sara A.; Csombordi, Rajmund; Komorowski, Jan; Diamanti, Klev (Uppsala University, 2021)
The dataset includes a PDF file containing the results and an Excel file with the following tables:

Table S1 Results of comparing the performance of MetaFetcheR to MetaboAnalystR using Diamanti et al.
Table S2 Results of comparing the performance of MetaFetcheR to MetaboAnalystR for Priolo et al.
Table S3 Results of comparing the performance of MetaFetcheR to MetaboAnalyst 5.0 webtool using Diamanti et al.
Table S4 Results of comparing the performance of MetaFetcheR to MetaboAnalyst 5.0 webtool for Priolo et al.
Table S5 Data quality test results for running 100 iterations on HMDB database.
Table S6 Data quality test results for running 100 iterations on KEGG database.
Table S7 Data quality test results for running 100 iterations on ChEBI database.
Table S8 Data quality test results for running 100 iterations on PubChem database.
Table S9 Data quality test results for running 100 iterations on LIPID MAPS database.
Table S10 The list of metabolites that were not mapped by MetaboAnalystR for Diamanti et al.
Table S11 An example of an input matrix for MetaFetcheR.
Table S12 Results of comparing the performance of MetaFetcheR to MS_targeted using Diamanti et al.
Table S13 Data set from Diamanti et al.
Table S14 Data set from Priolo et al.
Table S15 Results of comparing the performance of MetaFetcheR to CTS using KEGG identifiers available in Diamanti et al.
Table S16 Results of comparing the performance of MetaFetcheR to CTS using LIPID MAPS identifiers available in Diamanti et al.
Table S17 Results of comparing the performance of MetaFetcheR to CTS using KEGG identifiers available in Priolo et al.
Table S18 Results of comparing the performance of MetaFetcheR to CTS using KEGG identifiers available in Priolo et al.
(See the "index" tab in the Excel file for more information)

Small-compound databases contain a large amount of information for metabolites and metabolic pathways. However, the plethora of such databases and the redundancy of their information lead to major issues with analysis and standardization. Lack of preventive establishment of means of data access at the infant stages of a project might lead to mislabelled compounds, reduced statistical power and large delays in delivery of results.

We developed MetaFetcheR, an open-source R package that links metabolite data from several small-compound databases, resolves inconsistencies and covers a variety of use-cases of data fetching. We showed that the performance of MetaFetcheR was superior to existing approaches and databases by benchmarking the performance of the algorithm in three independent case studies based on two published datasets.

The dataset was originally published in DiVA and moved to SND in 2024.

The dataset includes a PDF file containing the results and an Excel file with the following tables:

Table S1 Results of comparing the performance of MetaFetcheR to MetaboAnalystR using Diamanti et al.
Table S2 Results of comparing the performance of MetaFetcheR to MetaboAnalystR for Priolo et al.
Table S3 Results of comparing the performance of MetaFetcheR to MetaboAnalyst 5.0 webtool using Diamanti et al.
Table S4 Results of comparing the performance of MetaFetcheR to MetaboAnalyst 5.0 webtool for Priolo et al.
Table S5 Data quality test results for running 100 iterations on HMDB database.
Table S6 Data quality test results for running 100 iterations on KEGG database.
Table S7 Data quality test results for running 100 iterations on ChEBI database.
Table S8 Data quality test results for running 100 iterations on PubChem database.
Table S9 Data quality test results for running 100 iterations on LIPID MAPS database.
Table S10 The list of metabolites that were not mapped by MetaboAnalystR for Diamanti et al.
Table S11 An example of an input matrix for MetaFetcheR.
Table S12 Results of comparing the performance of MetaFetcheR to MS_targeted using Diamanti et al.
Table S13 Data set from Diamanti et al.
Table S14 Data set from Priolo et al.
Table S15 Results of comparing the performance of MetaFetcheR to CTS using KEGG identifiers available in Diamanti et al.
Table S16 Results of comparing the performance of MetaFetcheR to CTS using LIPID MAPS identifiers available in Diamanti et al.
Table S17 Results of comparing the performance of MetaFetcheR to CTS using KEGG identifiers available in Priolo et al.
Table S18 Results of comparing the performance of MetaFetcheR to CTS using KEGG identifiers available in Priolo et al.

Se engelsk beskrivning för mer information.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Supplementary tables:MetaFetcheR: An R package for complete mapping of small compound data
Keywords: cell biology; cellbiologi; molecular biology; molekylärbiologi; data; data; Computer Sciences; Datavetenskap (datalogi); Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)